ЭПИК МАЙДОНДА РОМАНИЙ ТАФАККУР ТАЛҚИНИ - Бозоров, С. (SCIENCE and SOCIETY, 2020)
The article analyzes such concepts as the artistic function of the epic space in the creation of an artistic hero, the role of the hero in the formation of the character, based on the novel "In the steppe" by the talented writer Normurad Norkobilov. In the novel, the vitality of the views underlying the philosophical concepts arising from the unity of mankind and nature, is based on the example of theoretical views, such interpretations are more deeply reflected in the literature of the independence period. The concept of epic space has proven to be the basis for the formation of epic characters. These concepts were analyzed on the example of the main characters in the novel Tolanboy, Roziqul. It was analyzed that the changes in the character of the protagonists of the work were covered in the course of epic events
Keywords: epic field; artistic thinking; interpretation; analysis; evolution; character; emotional pain; art and skill